Housing price cycles in Poland – the case of 18 provincial capital cities in 2000–2020 - Trojanek, Radoslaw (International Journal of Strategic Property Management, 2021)
Using a unique dataset of 4,5 million offers, the housing cycles in 18 Polish provincial capitals were identified between 2000 and 2020 before and after the financial crisis. Differences in the course of the cycles depending on spatial diversity are presented, as well as differences in the strength of decreases and increases in individual phases. The examined housing markets in Poland have experienced significant variability in the extent of their cycles. One complete cycle was found in each of the analysed cities. Its average duration was approximately 12 years. In this cycle, residential prices (in real terms) increased by 88% on average, in the upward phase by 158%, while in the downward phase, they decreased by 27% in the cities under study. A correlation was found that implies that the higher the price rises in the upward period, the higher the price correction ensues in the cycle’s downward phase. Moreover, the similarity in fluctuations was present in the metropolitan markets in local housing markets, especially before the financial crisis. Apartment prices continued to grow by 2.9% on average in the real term during the COVID-19 pandemic in 2020.